The Effect Of Benson's Relaxation Technique On Pain Reduction In Post-Operative Cesarean Section Patients In The Postpartum Care Room At RSUD Dr. M.M Dunda - Ani Retni; Fahmi A. Lihu; Izrianingsri Dj. Yunus (Sean Institute, 2024)
The objective of this study is to determine the effect of Benson Relaxation Therapy on pain reduction in post-operative cesarean section patients in the Postpartum Care Room at RSUD dr. M.M Dunda. This research is a quantitative, analytical study aimed at understanding and predicting the effects of Benson's relaxation technique on pain reduction in post-cesarean patients. It uses a pre-experimental design with repeated measurements at pre-test and post-test stages. Conducted at RSUD dr. M.M Dunda in June 2024, the study involves 33 post-cesarean mothers from a population of 124. Non-probability sampling is used with specific inclusion and exclusion criteria. Data analysis includes univariate and bivariate tests, with normality testing via the Kolmogorov-Smirnov test. The study tests the hypothesis that Benson's relaxation technique reduces pain in post-cesarean patients, with a significance level of α = 0.05. Based on the research findings, the following conclusions can be drawn: First, prior to the Benson relaxation therapy, the average pain scale for postoperative cesarean section patients showed severe pain, with 16 patients (48.5%) experiencing this level of pain. Second, after undergoing Benson relaxation therapy, the average pain scale decreased, with 26 patients (78.8%) reporting mild pain. Lastly, there is a significant effect of Benson relaxation therapy on reducing pain in postoperative cesarean section patients in the postpartum ward at RSUD dr. M.M Dunda, as evidenced by a p-value of 0.000, which is less than 0.05.